Effect of low density lipoprotein on replacement of egg yolk in liquid preservation of mithun semen - PERUMAL, P; SRIVASTAVA, S K; GHOSH, S K; BARUAH, K K; KHAN, M H; RAJORIYA, J S; SRIVASTAVA, N (The Indian Journal of Animal Sciences, 2016)
This investigation explored the use of low density lipoproteins (LDL) from egg yolk (EY) in replacement EY on semen quality parameters (SQPs), velocity and motility parameters by Computer Assisted Sperm Analyzer (CASA) and biochemical parameters following liquid storage (5°C) of mithun semen. A total of 25 ejaculates collected from ten healthy mithun bulls and diluted with the standard tris citrate glycerol (TCG) extender were splited into three equal aliquots: Group 1, Control; EY, Group 2 and Group 3 contained 8 and 10% (w/v on dry weight basis) LDL, respectively. SQPs, CASA and biochemical parameters were evaluated following incubation of semen at 5°C. Results revealed a significant (P<0.05) improvement in these parameters in group 2 as compared to group 1 and 3. It was concluded that addition of 8% LDL (w/v) holds a clear advantage over EY or 10% LDL in preservation of mithun semen at liquid storage.